(untitled) (Journal of Information and Communication Technology, 2017)
Shoplifting can occur at any time and any place. From the big mall to a small shop, many security measures have been put in place as prevention tools. Apparently, there are numbers of shoplifting prevention tools in the market such as the Closedcircuit Television (CCTV), Electronic Article Surveillance (EAS) and Future Attribute Screening Technology (FAST). However, the cost issues and the ease of use always become the main concerns for the shopkeepers. Therefore CCTV was widely accepted because of the ease and affordable price. Although the CCTV is their main preference, it can be noted that CCTV operates in a static way where it can only records and monitor the incidents. This paper highlights the conventional CCTV issues and proposes the Intelligent Responsive Indoor System (IRiS) the as security crime prevention tool that uses face detection, recognition and behavior analysis to detect potential shoplifting intentions. Six small shop owners were interviewed to understand their insights on the problems and the need to further enhance the current CCTV. In addition, detailed discussions were provided in relation to the development of IRiS. Therefore, it can be suggested that IRiS provides a significant foundation and promises to be a security prevention tool to improve the conventional functions of the CCTV.